PENGARUH PERILAKU BERBAGI PENGETAHUAN, PERSEPSI DUKUNGAN ORGANISASI DAN PERSON JOB FIT TERHADAP PERILAKU INOVATIF - Dani Rizana (Majalah Imiah Manajemen & Bisnis, 2020)
This study aims to examine the effect of knowledge sharing behavior, perceptions of organizational support and person job fit on innovative behavior. The sample of this study was 150 employees of creative industry SMEs in Kebumen Regency. Hypothesis testing of this study was carried out using multiple linear regression analysis. The test results show that knowledge sharing behavior, organizational support perspectives, and person job fit have a positive effect on innovative behavior. The variable that has the most dominant influence is knowledge sharing behavior.